2019
DOI: 10.1080/13825585.2019.1664389
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of working memory for reinforcement learning in older adults varies with timescale of learning

Abstract: In young adults, individual differences in working memory (WM) contribute to reinforcement learning (RL). Age-related RL changes, however, are mostly attributed to decreased reward predictionerror (RPE) signaling. Here, we investigated the contribution of WM to RL in young (18-35) and older (≥65) adults. Because WM supports maintenance across a limited timescale, we only expected a relation between RL and WM with short delays between stimulus repetitions. Our results demonstrated better learning with short tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(43 citation statements)
references
References 73 publications
8
35
0
Order By: Relevance
“…Supporting this view, we previously found that after 3 weeks, associations that had been trained over multiple sessions were robust to forgetting, unlike associations trained in a single session . Similar effects were recently reported in a related study (van de Vijver and Ligneul, 2019). Notably, however, our current results indicate that spacing can be successfully studied in just a single session.…”
Section: Effect Of Post-learning Delay Periodsupporting
confidence: 92%
See 4 more Smart Citations
“…Supporting this view, we previously found that after 3 weeks, associations that had been trained over multiple sessions were robust to forgetting, unlike associations trained in a single session . Similar effects were recently reported in a related study (van de Vijver and Ligneul, 2019). Notably, however, our current results indicate that spacing can be successfully studied in just a single session.…”
Section: Effect Of Post-learning Delay Periodsupporting
confidence: 92%
“…Supporting this view, two previous studies have found effects of spacing after at least one week, allowing for sleep-related consolidation processes van de Vijver and Ligneul, 2019); here, training was either spaced across days or within a single session (van de Vijver and Ligneul, 2019). In the latter study, when a test was given immediately after learning, the authors found no change in performance from the end of learning (van de Vijver and Ligneul, 2019), aligning with the choice test results in our No-Delay group. By using a brief delay, however, our paradigm demonstrates that effects of spacing on the maintenance of learning can be successfully studied in just a single session.…”
Section: Effect Of Post-learning Delay Periodsupporting
confidence: 85%
See 3 more Smart Citations